Problems of Land Arrangement in River Boundary Areas (Study on the Winongo River, Bantul, Yogyakarta) - Hutabalian, Lyna R. (Sekolah Tinggi Pertanahan Nasional, 2024)
The river border area is part of the area that needs to be preserved as a protected area. Article 15 of Presidential Decree No. 32 of 1990, which governs the management of protected areas, mandates the protection of river boundaries to safeguard the river from human activities that could compromise its water quality, deteriorate the physical condition of its banks and bottom, and disrupt its flow. However, many river border areas still fail to comply with the river boundary regulations, including the Winongo River in Tirtonirmolo Village, Bantul, Yogyakarta. This article aims to elucidate the regulations and challenges associated with managing river border areas, assess the effectiveness of implementing existing regulations, and understand the perspectives of stakeholders involved in border area management. This article employs empirical legal methods, gathering data through interviews, field observations, studies of legal regulations, research documents, and other scientific literature. This study concludes that the river border area remains a significant issue due to its non-conformity with its designation, ineffective implementation of regulations, and the disparity among stakeholders in enforcing river border area regulations.